What Makes Small And Medium Enterprises Innovative? A Look At Knowledge Management - Hui, Grace Chua Beng (Journal of Knowledge Management Practice, 2012)
This study contributes to small medium growth-oriented companies by increasing the empirical understanding of how knowledge management practices affect their innovative capabilities. This study encourages practitioners to focus their KM initiatives especially on the three dimensions that had significant effect on innovation. The research is based on a conceptual model linking innovative capabilities, knowledge acquisition, knowledge dissemination and knowledge utilization. This study draws on empirical results from 125 Multimedia Super Corridor (MSC) companies using stratified sampling procedure. The results indicated that all three proposed knowledge management practices (knowledge acquisition, knowledge dissemination and knowledge utilization) were important for developing innovative capabilities.